Implikasi Praktik Autocratic Legalism terhadap Demokrasi, Keabsahan, dan Keadilan pada UU No. 17 Tahun 2023 Tentang Kesehatan - Amira Atsil Abigael Wegni; Novi Wulan Suci; Tabina Belinda Putri; Astri Maharani; Ayesta Intania; Citra Hayu Khatintri (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses the implications of Autocratic Legalism Practices for Democracy, Legality and Justice in Law no. 17 of 2023 concerning Health. This research aims to analyze whether the practice of autocratic legalism in Indonesia will have a direct impact on weakening the democratic system adopted by Indonesia. Autocratic legalism describes a person who has power at the legislative, executive and judicial levels by using hidden methods and hiding behind the law to take advantage of people's sovereignty and abandon the principles of constitutionalism, so the problem formulation of this analysis is how the practice of autocratic legalism has an impact on weakening democracy. and how the characteristics of autocratic legalism can impact the validity and fairness of legislative regulations. The benefit of the results of this analysis of autocratic legalism is to find out to what extent the practice of autocratic legalism in Indonesia threatens the principles of constitutionalism and has the potential to develop and spread widely in society and of course will have a negative impact on the democratic system and the validity and fairness of laws and regulations. This legal research uses normative juridical methods, namely based on the main legal materials in the form of theories, concepts, principles and statutory regulations related to the writing of this journal.